2021
DOI: 10.1007/s11356-021-14850-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organic extracts of seasonal PM2.5 on primary human lung epithelial cells and their chemical characterization

Abstract: Lung epithelial cells serve as the first line of defense against various inhaled pollutant particles. To investigate the adverse health effects of organic components of fine particulate matter (PM2.5) collected in Seoul, South Korea, we selected 12 PM2.5 samples from May 2016 to January 2017 and evaluated the effects of organic compounds of PM2.5 on inflammation, cellular aging, and macroautophagy in human lung epithelial cells isolated directly from healthy donors. Organic extracts of PM2.5 specifically induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…OC concentrations correlated significantly with adverse health effects, such as cardiopulmonary diseases, which require emergency hospitalization [ 24 , 25 ]. In addition, organic extracts of PM 2.5 collected in Seoul induced neutrophilic inflammation, cellular aging and enhanced macro autophagy in primary lung epithelial cells [ 26 ]. The biochemical effects of PM 2.5 rely on its multiple components and this is similarly likely for its adverse health effects which may vary depending on its chemical characteristics and where it is generated.…”
Section: Discussionmentioning
confidence: 99%
“…OC concentrations correlated significantly with adverse health effects, such as cardiopulmonary diseases, which require emergency hospitalization [ 24 , 25 ]. In addition, organic extracts of PM 2.5 collected in Seoul induced neutrophilic inflammation, cellular aging and enhanced macro autophagy in primary lung epithelial cells [ 26 ]. The biochemical effects of PM 2.5 rely on its multiple components and this is similarly likely for its adverse health effects which may vary depending on its chemical characteristics and where it is generated.…”
Section: Discussionmentioning
confidence: 99%
“…25 were observed to be significantly associated with IL6 among older adults with a confirmed history of coronary artery disease . Several in vitro laboratory studies have confirmed that PM 2.5 -bound PAHs, water-soluble organic nitrogen, n -alkanes, humic-like substances (HULIS), and secondary organic aerosols are significantly correlated with oxidative stress and inflammation. , However, related epidemiological evidence is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that these vary in cost, physiological relevance, and throughput. Studies have also looked at a variety of environmental pollutants including PM10, PM2.5, and PM0.1 (particulate matter with aerodynamic diameters of less than 10µm, 2.5µm, and 0.1µm, respectively) collected from cities including Beijing, Milan, Seoul and others (21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%